Asymptotic soliton train solutions of the defocusing nonlinear Schrödinger equation - Kraenkel, Roberto André [UNESP]; Kamchatnov, A. M. [UNESP]; Umarov, B. A. [UNESP] (Amer Physical Soc, 2002)
Asymptotic behavior of initially “large and smooth” pulses is investigated at two typical stages of their evolution governed by the defocusing nonlinear Schrödinger equation. At first, wave breaking phenomenon is studied in the limit of small dispersion. A solution of the Whitham modulational equations is found for the case of dissipationless shock wave arising after the wave breaking point. Then, asymptotic soliton trains arising eventually from a large and smooth initial pulse are studied by means of a semiclassical method. The parameter varying along the soliton train is calculated from the generalized Bohr-Sommerfeld quantization rule, so that the distribution of eigenvalues depends on two functions—intensity [formula presented] of the initial pulse and its initial chirp [formula presented] The influence of the initial chirp on the asymptotic state is investigated. Excellent agreement of the numerical solution of the defocusing NLS equation with predictions of the asymptotic theory is found. © 2002 The American Physical Society.